Is Hearing Loss in Infants Associated With Risk Factors? Evaluation of the Frequency of Risk Factors - Karaca, Çiǧdem Tepe (Clin Exp Otorhinolaryngol, 2014)
OBJECTIVES: To evaluate the frequency of risk factors and their influence on the evoked otoacoustic emission (OAE) of infants. METHODS: All newborns between November 2009 and June 2012 in Haydarpaşa Numune Education and Research Hospital were tested on distortion evoked OAE screening test. Total of 2,284 infants were examined. Sex, maternal infectious disease, birth type (vaginal birth or caesarean sectio), birth weight, familial hearing loss, intermarriage of parents, hyperbilirubinemia, intensive care were analyzed as risk factors. RESULTS: Total of 2,284 neonates were screened (1,220 males and 1,064 females) for the presence of OAE in both ears. Vaginal delivery, maternal infections during pregnancy, intermarriage of parents relative, low birth weight(<1,500 g) are related risk factors to failure of screening with OAE in our study. There was no statistically significant difference in sex ratios, birth weight, familial hearing loss, hyperbilirubinemia, and intensive care stay. CONCLUSION: Risk factors are only as useful as their predictive power. Not enough is known about which risk factors are relevant, which babies have the risk factors, or which babies will fail to attend follow-up, the effectiveness of targeted hearing loss testing is questionable at this point in time. A system needs to be developed to clarify which risk factors are discoverable, predictive and useful.